1999
DOI: 10.1097/00005768-199905000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ankle stabilizers affect ankle joint kinematics during drop landings

Abstract: The results indicate that some ankle stabilizers adversely affect ankle joint kinematics during landing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 15 publications
3
62
0
2
Order By: Relevance
“…These alterations led to the hypothesis that some ankle orthoses may reduce the ability of the ankle to absorb energy, and thereby increase the dissipation demands of the knee and hip joints. 28 This hypothesis parallels the speculation that the effective protection of the lower leg and ankle by ski boots promotes direct translation of the forces to the knee, 22 thereby explaining the high incidence of knee injury in skiers.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…These alterations led to the hypothesis that some ankle orthoses may reduce the ability of the ankle to absorb energy, and thereby increase the dissipation demands of the knee and hip joints. 28 This hypothesis parallels the speculation that the effective protection of the lower leg and ankle by ski boots promotes direct translation of the forces to the knee, 22 thereby explaining the high incidence of knee injury in skiers.…”
mentioning
confidence: 63%
“…28 Significant alterations in sagittal plane ankle joint kinematics during drop landings have been documented. 28 Specifically, reduced ankle plantar flexion at ground contact, reduced dorsiflexion during the impact phase of ground contact, and decreased maximum ankle velocity were revealed during testing of several ankle braces and tape. These alterations led to the hypothesis that some ankle orthoses may reduce the ability of the ankle to absorb energy, and thereby increase the dissipation demands of the knee and hip joints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…instrumentation A 7-camera, 240-Hz motion analysis system (Vicon Motion Systems and Peak Performance Inc, Oxford, UK) was used to obtain the 3-D kinematics during data collection. Anatomical reflective markers were used to define joint centers and placed at the left and right anterior superior iliac spines, superior iliac crests, posterior superior iliac spines, and greater trochanters, and right femoral epicondyle, right medial and lateral malleoli, and the right first and fifth metatarsal (eg, landing 21,25,32,33 and lateral cut 6,18,28 movements), during which ankle sprains typically occur. More recently, Cordova and colleagues 7 showed that a semirigid ankle brace is more effective in reducing rearfoot angular displacement and velocity than a lace-up brace, but the lace-up brace was more effective than no brace.…”
Section: Participants Amentioning
confidence: 99%
“…Taping helps to protect and support joints while they perform functional movement [21]. Taping can also help increase kinetic stability of movement [22]. According to previous studies on taping in post-stroke patients, during the stance phase gait, application of gluteal taping resulted in improvement in hip joint extension [23].…”
Section: Introductionmentioning
confidence: 98%